Role of the functional status of the autonomic nervous system in the clinical course of purulent meningitis - D. A. Zadiraka; O. V. Ryabokon (Patologìâ)
Purulent meningitis is defined by high indices of sickness and lethality rates, a great risk of cerebral and extracerebral complications development, steady residual consequences formation. During neuroinfections, the state of adaptation mechanisms, which is characterized by exhaustion of regulatory systems with the development of decompensation, plays a crucial part. Heart rate variability clearly reflects the degree of regulatory system tension caused by the influence of both physiological and pathological factors.